Suppression of the anomalous relationship between diffusivities of cations and anions by water in imidazolium-based ionic liquids - Menjoge, Amrish; Vasenkov, Sergey (Diffusion Fundamentals, 2009)
Proton pulsed field gradient (PFG) NMR technique at high magnetic field (17.6 T) and high magnetic field gradients (up to 30 T/m) is applied to study diffusion of the anions and cations in the ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate ([Emim][ETSO4]) with and without water. Excellent NMR spectral resolution attained by this technique allowed high-precision monitoring of the diffusivities of the anions, cations and water in a single experiment. The PFG NMR data show that the anomalous relationship between the ion diffusivities, i.e. larger self-diffusion coefficient of the bulkier [Emim] cation than that of the less bulky [ETSO4] anion, becomes much less pronounced due to addition of water into the ionic liquid. This observation is explained by the distortion of the local structure in the ionic liquid by water molecules leading to a possible loss of the diffusion anisotropy for the cation diffusion. The reported experimental data are in a qualitative agreement with the most recent results of molecular dynamics simulations (see references 9 and 10).